The impact of the covid-19 pandemic on essential public healthcare services in Gauteng province, South Africa - Fonka, Cyril Bernsah (My University, 2024)
Background: The Covid-19 pandemic like previous outbreaks has the potential to adversely impact essential healthcare services. Even though the Gauteng province was considered the epicentre of the Covid19 outbreak in South Africa, there is no comprehensive assessment of the effect of Covid-19 on the service utilisation, delivery and health outcomes of routine healthcare services in Gauteng province. Aim: To assess the impact of the Covid-19 pandemic on the utilisation, delivery and health outcomes of essential maternal, neonatal and child health (MNCH) services in Gauteng province, South Africa. Methods: This was a mixed methods study. A longitudinal study design was used to analyse data from the District Health Information Software (DHIS). We compared key MNCH indicators in the pre-Covid-19 period (March 2019-February 2020) to corresponding periods during the Covid-19 outbreak (March 2020- February 2021). The differences were analysed using time plots, linear regression, and Interrupted Time Series Analysis (ITSA) in Stata 17.0, at a 5% level of alpha for statistical significance. In-depth interviews were conducted with senior managers in the Gauteng Department of Health (GDoH) using MS Teams, to explore their perspectives on the impact of Covid-19 on routine healthcare services in the province and their recommendations for dealing with future pandemics. The interviews were recorded, transcribed, coded and analysed thematically using MS word 2016. Results: The Covid-19 pandemic disrupted the utilisation of essential MNCH services in the Gauteng province. The disruption was observed in the time trend plots, and then quantified by comparing the indicator means for the 12-month periods before and during Covid-19. The impact was a statistically significant decline in the mean of three indicators: PHC headcount <5 years declined by 77 103.9 visits (p<0.001), ANC 1st visits before 20 weeks decreased by 3.0% (p=0.002) and PNC visits within 6 days decreased by 10.2% (p<0.001) (Error! Reference source not found.). The ITS regression provided a more nuanced analysis. The decrease in PHC headcount t <5 years and PNC visits within 6 days were due to the immediate effect of the March 2020 Covid-19 lockdown which led to a drop in utilisation services. However, the effect on ANC 1st visits before 20 weeks was a continuous decline in utilisation throughout the Covid-19 period (Error! Reference source not found.). Service delivery and outcome indicators were negatively affected though not significantly. There were no significant recoveries and some indicators rather became worse post-lockdown. The nature of the adverse impact of Covid-19 on MNCH indicators was similar across all five districts, although the degree of disruption varied among the districts and services. The decline in service utilisation for PHC headcount <5 years ANC 1st visits before 20 weeks and PNC visits within 6 days was statistically significant in all districts, except for ANC 1st visits in Johannesburg (Error! Reference source not found.). The decline in PHC headcount <5 years was significantly larger in the three metropolitan districts (Johannesburg, Ekurhuleni and Tshwane) compared to the two non-metropolitan districts (Sedibeng and West Rand) (Table 5). ANC 1st visits before 20 weeks significantly declined in the Ekurhuleni, Sedibeng and West Rand districts compared to Johannesburg. While the decrease in PNC visits within 6 days significantly deteriorated in Johannesburg compared to the other four districts (Error! Reference source not found.). Pneumonia fatality <5 years significantly declined in the pooled analysis, in the Tshwane district alone. The majority of the respondents agreed that the Covid-19 pandemic disrupted essential healthcare services but a few disagreed. Several reasons were advanced for the disruption. On the supply side, they included: (i) the reallocation of resources to fighting Covid-19; (ii) healthcare worker shortages due to Covid-19 illness; (iii) healthcare facilities turning away non-Covid-19 patients; and (iv) Covid-19 screening that increased waiting times. On the demand side are; (i) restrictions on movement and limited public transport during the lockdown; (ii) fears of being infected by Covid-19 at health facilities; and (iii) misinterpretation of health information about the availability of non-Covid services. According to the respondents, the disruption of essential healthcare services had significant consequences, particularly for chronic patients, including treatment interruption, loss of follow-up, and death. The ‘catch-up’ plan and technology were used to improve service delivery during Covid-19. Conclusion: The Covid-19 pandemic disrupted the utilisation of essential healthcare services for MNCH. Although service delivery and health outcomes were less impacted, some outcome indicators at district levels went worst. While there were recovery attempts for service delivery like immunisation, some services rather deteriorated post-Covid-19 lockdown. However, there were mixed findings, fewer routine services were not affected by Covid-19. It is important to continuously assess and redress the unintended impacts of outbreaks even while they are occurring. This requires an understanding of the reasons and mechanisms of service disruption from demand and supply perspectives. Critical policies like lockdowns should be a collective decision, implemented without undermining routine services. High-level policymakers must consider addressing geographical variations of an outbreak’s impact on essential healthcare services. Covid19 may have more complex long-term effects, especially for individuals with adverse social determinants. And it may take longer for some healthcare services to fully recover hence, the need for health systems interventions to prioritise the affected services.
A research report submitted in partial fulfilment of the requirement for the degree of Masters of Public Health (Health Economics) to the Faculty of Health Sciences, University of the Witwatersrand, School of Public Health, Johannesburg, 2023
Keywords: Essential healthcare services; Lockdown; Covid-19; SDG-3: Good health and well-being